Effect of active resisted 30 m sprints upon step and joint kinematics and muscle activity in experienced male and female sprinters - van den Tillar, R. (Journal of Sports Sciences, 2021)
This study compared the kinematics (step and joint) and muscle activity of unresisted and active resisted 30 m sprints with different loads (10-40% body mass) in experienced male and female sprinters. Step kinematics were measured using a laser gun and contact mat in 28 male and female participants during unresisted 30 m sprint, and sprints with 10-40% of body mass (BM) active resistance, while peak angular velocities of lower limb was measured, together with muscle activation of nine muscles. Increased resisted loads resulted in slower 30 m times, as a result of lower step velocity mainly caused by shorter step lengths and frequencies, flight times and longer contact times, with a greater effect on women than on men. These step kinematic differences, due to increasing load were accompanied with lower peak joint movements. However, gender differences were only found for peak plantar flexion with unresisted and 10% BM resisted sprints. Furthermore, increasing load decreased calf and hamstring muscles activity, while medial vastus activity increased. Based upon these findings, it was concluded that when introducing active resisted sprints, women should sprint with approximately 10% less active loads than men to have equal step and joint kinematics development over the sprint distance.